Tinjauan Keakuratan Kode Diagnosis Neoplasma Di RSUD Banjarbaru - Irmawan, Irmawan; Kristina, Sabar; Qorbaniati, Nita; Husada Borneo, STIKES; STIKES Husada Borneo, Alumni (Jurnal Kesehatan Indonesia, 2014)
Introduction : Banjarbaru Public Hospital, in medical record patient with a neoplasma diagnosis is not inclusion morphology code. Morphology code must include in medical record. There is a code behavior in morphology code after the slash or solidus (/), which shows a malignant, benign, in situ, or uncertain whether malignant or benign. This research is taking place in Banjarbaru Public Hospital, for about 1 (one) month, from June 13 th until July 13 th 2013.Method : This research is descriptive research, using a accidental sampling technique with outcome 100 inpatient medical record as a sample, with a data collection technique by observation (check list), and interview, using unvaried analysis and present by a number.Result : The research output is accuracy percentage of neo plasma code which include a histology code is 26 % of medical record is in unsuitable category and medical record which is include ICD (adding morphology and histology code) 0 % is in a very unsuitable category and for medical record that only include morphology code is 0 % is in a very unsuitable category too. The output from neo plasma diagnosis code is use as a disease index, RL 2 report and if possible can be use in the most 10 diseases.Conclusion : Suggestion from this research is neoplasma diagnosis on inpatient medical record to explain the morphology and for neoplasma morphology is using a code according by ICD-O.